Shining light on polarizable dark particles - Fichet, Sylvain [UNESP] (Springer, 2017)
We investigate the possibilities of searching for a self-conjugate polarizable particle in the self-interactions of light. We first observe that polarizability can arise either from the exchange of mediator states or as a consequence of the inner structure of the particle. To exemplify this second possibility we calculate the polarizability of a neutral bosonic open string, and find it is described only by dimension-8 operators. Focussing on the spin-0 case, we calculate the light-by-light scattering amplitudes induced by the dimension-6 and 8 polarizability operators. Performing a simulation of exclusive diphoton production with proton tagging at the LHC, we find that the imprint of the polarizable dark particle can be potentially detected at 5 sigma significance for mass and cutoff reaching values above the TeV scale, for root s = 13 TeV and 300 fb(-1) of integrated luminosity. If the polarizable dark particle is stable, it can be a dark matter candidate, in which case we argue this exclusive diphoton search may complement the existing LHC searches for polarizable dark matter.
Keywords: Forward physics; Dark matter; Hadron-Hadron scattering (experiments); proton-proton scattering